2014
DOI: 10.1186/1756-0500-7-410
|View full text |Cite
|
Sign up to set email alerts
|

Hirschsprung’s disease in children: a five year experience at a University teaching hospital in northwestern Tanzania

Abstract: BackgroundHirschsprung’s disease (HD) is the commonest cause of functional intestinal obstruction in children and poses challenges to pediatricians and pediatric surgeons practicing in resource-limited countries. This study describes the clinical characteristics and outcome of management of this disease in our setting and highlights challenges associated with the care of these patients and proffer solutions for improved outcome.MethodsThis was a descriptive prospective study of children aged ≤ 10 years who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 27 publications
7
31
1
5
Order By: Relevance
“…Mabula et al have reported their majority of patients after one year of life. [13] This study also showed that males were more afflicted by the disease as reported in the literature. [14] In our study we found males to be affected more than females.…”
Section: Discussionsupporting
confidence: 76%
“…Mabula et al have reported their majority of patients after one year of life. [13] This study also showed that males were more afflicted by the disease as reported in the literature. [14] In our study we found males to be affected more than females.…”
Section: Discussionsupporting
confidence: 76%
“…Early diagnosis will help in decreasing morbidity and mortality associated with the disease. 1 This retrospective observational study on HD cases diagnosed in a tertiary care teaching hospital was conducted to develop a profile for Hirschsprung's disease in Indian population based on insights about its incidence in different age groups and gender distribution and its diagnosis by biopsy. This profile will help in the diagnosis of HD in adults which is often missed.…”
Section: Discussionmentioning
confidence: 99%
“…Hirschsprung's disease is a developmental defect of the enteric nervous system. 1 It is one of the frequent causes of intestinal obstruction in newborns, secondary to gut motility disorder. It has features of complex genetic heterogeneous disorder with variable inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…In the pathogenesis of HD, the migration arrest of enteric neural crest cells (ENCCs) is prominent, leading to the failure of reaching to the hindgut during embryogenesis. A total of 98% of neonates pass meconium within 24-48 hours after birth, while this fails in patients with HD [21]. There are various techniques for managing the disease.…”
Section: Discussionmentioning
confidence: 99%